ANALISIS PARTISIPASI GURU PPKN DALAM MENINGKATKAN KEDISIPLINAN WAKTU DALAM MELAKSANAKAN PROSES PEMBELAJARAN - Laia, Hendika Heneti (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The rationale behind this research is that instructors have a significant impact on molding the nation's character and fostering the potential of children. Students' potential is cultivated in accordance with their unique qualities and abilities, with the aim of fostering their personal growth and maximizing their developmental progress. Students in teacher education are required to possess proficiency in designing and executing impactful instruction to enhance students' capabilities, enabling them to become self-reliant and adaptable individuals. In order to cultivate pupils who are both intelligent and adaptable, it is essential to foster the entire development of their potential. This can be accomplished through effective instruction, which involves delivering comprehensible and engaging lessons that enable students to successfully comprehend and grasp the offered content. designated proficiencies. Effective collaboration between teachers and students is essential for a successful learning experience. This research employs a qualitative and descriptive research methodology. The data sources utilized in this research included the school principal as the primary respondent, as well as teachers and four kids who served as informants. Specifically, this study relied on responses from the school administrator, a teacher, and four students who served as informants. First, there was observation; second, there were interviews; and third, there was a documentation study to gather the data. There are three separate phases to data analysis: (1) data reduction, which entails making the data as simple and concise as possible; (2) data presentation, which entails making the data visually appealing; and (3) conclusion drawing, which entails making final conclusions and insights based on the analysed data. Without instructors, students would be directionless, as teachers are the ones who instill the qualities that make individuals successful in the field of education, such as discipline and time management.The rationale behind this research is that instructors have a significant impact on molding the nation's character and fostering the potential of children. Students' potential is cultivated in accordance with their unique qualities and abilities, with the aim of fostering their personal growth and maximizing their developmental progress. Students in teacher education are required to possess proficiency in designing and executing impactful instruction to enhance students' capabilities, enabling them to become self-reliant and adaptable individuals. In order to cultivate pupils who are both intelligent and adaptable, it is essential to foster the entire development of their potential. This can be accomplished through effective instruction, which involves delivering comprehensible and engaging lessons that enable students to successfully comprehend and grasp the offered content. designated proficiencies. Effective collaboration between teachers and students is essential for a successful learning experience. This research employs a qualitative and descriptive research methodology. The data sources utilized in this research included the school principal as the primary respondent, as well as teachers and four kids who served as informants. Specifically, this study relied on responses from the school administrator, a teacher, and four students who served as informants. First, there was observation; second, there were interviews; and third, there was a documentation study to gather the data. There are three separate phases to data analysis: (1) data reduction, which entails making the data as simple and concise as possible; (2) data presentation, which entails making the data visually appealing; and (3) conclusion drawing, which entails making final conclusions and insights based on the analysed data. Without instructors, students would be directionless, as teachers are the ones who instill the qualities that make individuals successful in the field of education, such as discipline and time management.